Image Segmentation Using K- Means Clustering Method for Brain Tumour Detection - Thylashri, S; Mahesh Yadav, Udutha; Danush Chowdary, T (International Journal of Engineering and Technology, 2018)
Brain tumour is an irregular development by cells imitating among them in an unstoppable way. Specific identification of size and area of Brain tumour assumes a fundamental part in the analysis of tumour. Image processing is a dynamic research territory in which processing of image in medical field is an exceedingly difficult field. Segmentation of image assumes a critical part in handling of image as it helps in the finding of suspicious districts from the restorative image. In this paper a proficient algorithm is proposed for detection of tumour based on segmentation of brain by means of clustering technique. The main idea in this clustering algorithm is to transferÂ a given gray-level image and then separateÂ tumour objects positionÂ from other items of an MR image by using K-means clustering. Experiments say that segmentation for MR brain images can be done to help medical professionals to identify exactly size and region of the tumour located area in brain.Â Â